Incidence and characteristics of injuries in elite Australian junior rugby league players - Orr, R.; Cheng, H. L. (Journal of Science and Medicine in Sport, 2016)
Objectives: Rugby league (RL) is a physically demanding collision sport, yet few studies describe injuries at the junior level despite their potential impact on career pathways and long-term health. With the absence of an injury surveillance paradigm in junior competition, this study aimed to investigate injury incidence in an Australian setting. Design: Prospective cohort study. Methods: A set of injury surveillance forms were developed and used to record injury characteristics, mechanism, severity and follow-up throughout one season. Results: Junior RL players (n = 368, age: 15.8 ± 1.0 years) from 15 clubs provided baseline information. Of these, approximately six clubs (n = 122) provided longitudinal injury data. A total of 109 injuries (90% match-related) were recorded, with the tackle accounting for 61%. Injury incidence (37.1 injuries per 1000 match hours) was consistent with previous literature. Most injuries did not result in missed matches. The ankle and head/face were most frequently injured (both 13%), with ankle injuries leading to the highest losses of match-play. Contusions were common (38%), although ligament injuries caused the greatest match-play losses. Injury site significantly differed between forwards and backs (p = 0.003), with forwards sustaining more head/face and sternum injuries, and backs more ankle injuries. Injury type (p = 0.25) and severity (p = 0.09) were similar between positions. Conclusions: Given the ongoing biological maturation in adolescent players and the injury risks related to RL, playing intensity, training regimes and injury incidence warrant rigorous documentation and monitoring. This study argues for functional but low-burden injury surveillance systems (e.g. electronic platforms) to be developed and implemented in junior RL.